Estudo dos potenciais auditivos de tronco encefálico na toxoplasmose congênita diagnosticada e tratada precocemente - Aline Almeida Fontes (2016)
Recent studies have shown the occurrence of hearing loss in children with congenital toxoplasmosis, and that this infection is a potential risk factor for hearing loss. The Hearing Disorder (HD) can generate deficits in the development of speech and language, and in order for this development, a full hearing is required. In Brazil, all newborns must be assessed by the Universal Newborn Hearing Screening (UNHS), which has become mandatory by the Federal Law No. 12,303, which aims early identification of hearing loss in the first months of life. Hearing screening has been performed with the association between transiently evoked otoacoustic emissions (TEOAE) and the investigation of the Auditory Brainstem Response (ABR). In addition to allow an investigation of babies hearing, these tests have been used in infants with and without risk factors for HD. In this perspective, the objective of this study was to investigate the hearing of infants with 1 - 3 months of age with congenital toxoplasmosis (those at risk of developing HD) by evaluating the ABR, and to compare the results with those babies in the same age without infection. It is a comparative study with non-probabilistic sample consisting of 100 infants, divided into 2 groups. The first group was composed of 47 infants diagnosed with congenital toxoplasmosis confirmed by the presence of IgM and / or IgA through the dry blood collection; and the second group was composed of 53 infants without the diagnosis of congenital toxoplasmosis. All babies with congenital toxoplasmosis were evaluated by the central nervous system image test and received early treatment. All babies were submitted to hearing assessment procedures: anamnesis, OET, ABR and automatic ABR. In the final analysis, 76 children were included, 37 of those had congenital toxoplasmosis and 39 did not have congenital toxoplasmosis. The excluded babies have not completed at least one of the tests performed in this study. The results showed that the groups were similar in age and gender. Of the 37 babies with toxoplasmosis, 3 had altered neurological examination. At the ABR evaluation, 2 children without toxoplasmosis and 10 children with congenital toxoplasmosis presented results that suggested alteration in the maturational process of the brainstem auditory pathway. This research demonstrates the importance of early investigation of hearing in infants with congenital toxoplasmosis through the hearing screening, which allows diagnosis before 3 months and intervention before 6 months of age for infants with hearing deficiency. It was concluded that the ABR has proved to be a complementary tool in the evaluation of hearing of the children with toxoplasmosis. It was found that 27% (n = 10) of the children were identified with possible unilateral change in ABR, and that children with toxoplasmosis, between 1 and 3 months old, are 5 times more likely to present changes in the ABR than other children of the same age range without that infection.